A descriptive study on the thoroughness of the University of the Philippines College of Dentistry practicing graduates in the performance of patient work-up - Santos, Sarah L.; Yabut, Maria Consolacion C.; Magtanong, Danilo L. (Adviser).
Performing a thorough patient work-up is vital in the formulation of diagnosis and treatment plan. It also prevents medical emergencies and treatment failures. This study aimed to know if practicing graduates of UPCD are thorough in the conduction of patient work-up. Purposive sampling was done wherein 30 dentists who graduated within 1988-1998 and are alumni of UPCD, were asked to answer a questionnaire. Interview and a copy of a blank chart that the dentists use in their private practice supported the questionnaire. To assess the thoroughness of the dentist in conducting a patient work-up, scores were given to every question the dentist answered. The scores showed that none of the dentist-subjects were able to get a perfect score, therefore none of them perform a thorough patient work-up.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental Records; Patient work-up.